An Analysis of Scientific Literacy on High School Students of Demak Regency in Biology Lessons - Prasetyo, Dwi; Pukan, Krispinus Kedati; Ngabekti, Sri (Journal of Biology Education, 2020)
The study aims to analyze students' scientific literacy level on knowledge, competencies, and attitudes aspect, also analyzing the correlation between scientific literacy aspects of knowledge with competencies, attitudes with competencies, knowledge with attitudes. The study was conducted using a survey method with a cross-sectional design. The entire student of class XI MIPA of State High Schools in Demak regency academic year 2017/2018 were chosen as the population. The method in taking the sample was Stratified Random Sampling. The sample of the study is 304 students. Test, questionnaire, documentation, and interview were methods used in collecting the data. The result showed that students' scientific literacy level on knowledge at 37,54% on the Ã¢â‚¬Å“lowÃ¢â‚¬Â category, students' competencies at 36,75% on the Ã¢â‚¬Å“lowÃ¢â‚¬Â category, and students' attitudes at 68,11% on the Ã¢â‚¬Å“goodÃ¢â‚¬Â category. Correlation test results between scientific literacy aspects of knowledge with competencies obtained correlation coefficient at 0,534, between attitudes and competencies obtained correlation coefficient at 0,172, between attitudes with knowledge obtained correlation coefficient at -0,094. Based on the result, the level of students' scientific literacy on knowledge and competencies aspects were classified in the low category. The level of students' scientific literacy on attitudes aspect was classified in the good category. The correlation between knowledge with competencies aspect has a positive correlation in the medium category. The correlation between attitudes with competencies aspect has a positive correlation in the very weak category. But, the correlation between knowledge with attitudes aspect was not correlated.